A new species of Aleurocanthus Quaintance & Baker (Homoptera: Aleyrodidae) from Areca catechu in India, with comments on the status of Aleurodes nubilans Buckton - David, B. Vasantharaj; Manjunatha, M. (Zootaxa, 2003)
A new species of whitefly, Aleurocanthus arecae sp. nov., collected from arecanut (Areca catechu) in Karnataka state in India, is described and illustrated. The status of Aleurodes nubilans Buckton is discussed and considered a nomen dubium.